Respuesta :
Answer:
(3, -1)
Step-by-step explanation:
Given
- 4x + 5y = 7
- y = 3x - 10
Subbing the value of y
- 4x + 5(3x - 10) = 7
- 4x + 15x - 50 = 7
- 19x = 57
- x = 3
- y = 3(3) - 10
- y = 9 - 10
- y = -1
- Solution is (3, -1)
Answer:
- x = 3
- y = -1
Solution: (3, -1)
Step-by-step explanation:
Given equations:
- [tex]4x + 5y = 7[/tex]
- [tex]y = 3x - 10[/tex]
Step-1: Reorganize the equations with "y" on the L.H.S
[tex]\rightarrow \left \{ {{4x + 5y = 7} \atop {y = 3x - 10}} \right.[/tex]
[tex]\rightarrow \left \{ {{5y = 7 - 4x} \atop {y = 3x - 10}} \right.[/tex]
[tex]\rightarrow \left \{ {{5y = 7 - 4x} \atop y =-10 + 3x}} \right.[/tex]
Step-2: Make the x-variables the same on both equations
[tex]\rightarrow \left \{ {{3(5y = 7 - 4x)} \atop 4(y =-10 + 3x)}} \right.[/tex]
[tex]\rightarrow \left \{ {{15y = 21 - 12x} \atop 4y =-40 + 12x}} \right.[/tex]
Step-3: Add the equations
[tex]\rightarrow (15y + 4y) = (21 - 40) + (-12x + 12x)[/tex]
[tex]\rightarrow 19y = -19[/tex]
Step-4: Divide both sides by 19
[tex]\rightarrow \dfrac{19y}{19} = \dfrac{-19}{19}[/tex]
[tex]\rightarrow y = -1[/tex]
Step-5: Substitute the value of y into any equation
[tex]\rightarrow y = 3x - 10[/tex]
[tex]\rightarrow -1 = 3x - 10[/tex]
Step-6: Simplify the equation
[tex]\rightarrow -1 + 10 = 3x[/tex]
[tex]\rightarrow9= 3x[/tex]
Step-7: Divide 3 both sides
[tex]\rightarrow \dfrac{9}{3} = \dfrac{3x}{3}[/tex]
[tex]\rightarrow x = 3[/tex]
(Optional) Step-8: Convert the solution(s) into (x, y) form
[tex]\rightarrow (x, y) \rightarrow (x = 3; y=-1) \rightarrow (3,-1)[/tex]
Thus, the value of x and y is 3 and -1. The solution is (3, -1).